Visualizing Bibliometric Networks on Green Advertising Literature: What we know and what we do not know - Prithvi Natesan Paulraj GS; Anna Joy (International Journal of Engineering and Management Research, 2024)
This article aims to perform a bibliometric analysis of the extant research in the area of green advertising to identify the dominant themes and research gaps in the said area. For the purpose of the study, 220 articles were sourced from the Scopus database after running a search query using designated keywords. This study examines the literature on green advertising over the last few years and reviews the published documents using VOSviewer software. While shortlisting the research articles, open-access articles, conference papers, and papers written in other languages were discarded. The study shows the key research trends in the area of green advertising, in terms of parameters like co-author analysis, keyword analysis, country analysis, and organizational analysis. Journal of Advertising, International Journal of Advertising and Sustainability are the leading journals publishing papers in the area of green advertising. China, the United States, and Korea play a major role in research on this topic, with the highest number of corresponding authors coming from these three countries. The findings provide useful insights to academicians in terms of directions for further research that needs to be done.